Conversion of Chitin to Defined Chitosan Oligomers: Current Status and Future Prospects - Christian Schmitz; Lilian González Auza; David Koberidze; Stefan Rasche; Rainer Fischer; Luisa Bortesi (Marine Drugs, 2019)
Chitin is an abundant polysaccharide primarily produced as an industrial waste stream during the processing of crustaceans. Despite the limited applications of chitin, there is interest from the medical, agrochemical, food and cosmetic industries because it can be converted into chitosan and partially acetylated chitosan oligomers (COS). These molecules have various useful properties, including antimicrobial and anti-inflammatory activities. The chemical production of COS is environmentally hazardous and it is difficult to control the degree of polymerization and acetylation. These issues can be addressed by using specific enzymes, particularly chitinases, chitosanases and chitin deacetylases, which yield better-defined chitosan and COS mixtures. In this review, we summarize recent chemical and enzymatic approaches for the production of chitosan and COS. We also discuss a design-of-experiments approach for process optimization that could help to enhance enzymatic processes in terms of product yield and product characteristics. This may allow the production of novel COS structures with unique functional properties to further expand the applications of these diverse bioactive molecules.